Sustaining the right to privacy in E-Commerce environment: The legal approach - Mohamed, Duryana (Ontario International Development Agency, 2012)
The right to privacy is a fundamental human right as declared in Article 12 of the Universal Declaration of Human Rights and Article 17 of the International Covenant on Civil and Political Rights. Some countries recognise this right as constitutional right of individuals. The importance of this right is also underlined with the enactment of legislation by most countries. In Malaysia, the privacy protection is available under the Personal Data Protection Act passed in 2010. This Act seeks to regulate the processing of personal data of individuals involved in commercial transactions by data users so as to provide protection to the individual’s personal data, thereby safeguarding the interests of such individual. Since this privacy right is important in e-commerce, this paper will examine the extent of privacy protection available under the existing law and whether such law and other relevant laws provide adequate protection to the personal data when dealing with online transaction. The aim of this paper is to establish justice to the online consumers and to provide information that their right is protected under the law.